Characteristics and performance of two-dimensional materials for electrocatalysis - Chia, Xinyi (2020)
The unique anisotropy and electronic properties of 2D materials have sparked immense interest in their fundamental electrochemistry and wide spectrum of applications. Beginning with the prototype 2D material — graphene — studies into an extensive library of other ultrathin layered structures have gradually emerged. Among these are the transition metal dichalcogenides, layered double hydroxides, metal carbides and nitrides (MXenes) and the black phosphorus family of monoelemental compounds. In this Review, we discuss the similarities of these 2D materials and highlight differences in their electrochemical and electrocatalytic properties. Recent progress on 2D materials for energy-related electrocatalysis in industrially important reactions is presented. Together this shows that dimensionality and surface characteristics are both vital aspects to consider when designing and fabricating compounds to achieve desired properties in specific applications.